Investigation of the behavior of gadolinium complexes in plastic scintillators - Velmozhnaya, E.S.; Bedrik, A.I.; Zhmurin, P.N.; Titskaya, V.D.; Adadurov, A.F.; Sofronov, D.S. (Functional Materials, 2013)
This paper presents results on investigation of characteristics of plastic scintillators that contain carboxylates of aliphatic-aromatic acid with different neutral ligands as Gd-containing compounds. The peculiarities of these compounds synthesis were shown. The compounds thermal stability and solubility in styrene were investigated. Optimal conditions for Gd-containing polystyrene-based scintillators obtaining were developed.